Influence of Morphology on Angle of Internal Friction in Slags - J. Logeshwari; P. V. Sivapullaiah (Recent Progress in Science and Technology Vol. 9, 2023)
The performance of any granular material is determined by its morphological parameters, as well as its physical and chemical properties. Slags from the iron and steel industries are used for this study, and their morphology is compared to their angle of internal friction. These parameters are determined using ImageJ software on slag samples. The morphological parameters are roundness, sphericity, and surface roughness. According to the literature, particles with elongated, angular, and rough surfaces are expected to be more resistant to shearing than spherical, round, and smooth particles. This paper concludes that roundness values in slags, rather than sphericity, are in trend with friction angle. It is also observed that regardless of sphericity or roundness, the angle of internal friction remains within a narrow range. Certain particles, which are prone to crushing under load, will not behave as expected based on their shape parameters. As a result, the shape parameters alone may be insufficient to adequately represent the frictional characteristics. ImageJ is a 2D particle analysis programme. Even if 3D analysis is performed, there is no guarantee that the particle will behave as expected because particle orientation also plays a significant role in its mechanical behaviour.